Potential Application of Fabric Waste as Acoustic Materials in Building - Ahmad Jailani, Muhammad Ersyad; Mohd Isa, Mohd Hafizal (MAJ - Malaysia Architectural Journal, 2020)
The study aims to identify the potential of fabric waste to be converted into acoustic material to solve the problem of noise pollution. In a human’s environment, acoustic comfort is one of the basic needs. The sound that is too high in decibel may create noise and harms the humans’ hearing ability to the point it is called noise pollution. It can be argued that noise presents more negative effects on humans’ health may it be physically or mentally affected. Millions of people are not excluded from being affected by noise pollution, which not only causing annoyance but also harming public health. The sound absorption coefficient measurement method is adopted in this study. The results show that fabric waste has the ability to absorb sound, eventually, reduce noise pollution. Cotton is one of the types of fabrics that shows better sound-absorbing efficiency compared to other materials. The use of acoustic panel is crucial in keeping the balance of comfort in humans’ lives at the same times improving the environment.